Systematic Construction of Semantic Structure Computationally Digital Communication Systems As A Model - Aida Haouchi (The Journal of Studies in Language, Culture and Society, 2024)
Our study deals with the systematic construction of the structural representation of meaning, as it is based on a basic topic, which is structure, as it goes beyond the representation of meaning for its parts, as logical representations are usually used to perform automatic inferences according to the appropriate theoretical confirmation. Also, the transition from the ordinary level of meaning towards the automatic discovery of knowledge is a closely intertwined designation between the two features. Because resources that were created non-automatically are automatically extended or merged. How is that? This occurs by directing the automated search to semantic information and restricting it to non-automatically specified information. From here, logical representations of data are created at the intersection of non-automated specification and automated tuning; This has generated many questions about the computational structure of semantics and how it works. Do we get better and deeper semantic analysis because we use specific linguistic knowledge in a non-automatic manner, or is the future in powerful communicative digital models that perform a complete task from natural language inputs and outputs alone without pre-defined linguistic knowledge?